Managing sustainably - Benn, Suzanne (Henry Stewart Talks, 2010)
Strong and weak discourses of sustainability, Sustainability in the organizational context, Is sustainability possible?, Case examples of organizational change and learning for sustainability, Debates and challenges
Reviewed at 2018/10/31